Abdullah Saeed’s Contextual Restructures of The Qur’an - Muhammad Hatta (International Journal of Islamic Thought and Humanities, 2023)
This paper tries to explain Abdullah Saeed's ideas with a new approach to interpreting the Qur'an, namely an approach called the contextualist approach. In Abdullah Saeed's perspective, there has been a gap between the text that has been understood literally by most scholars and the socio-historical context of the Qur'an at the time the revelation was revealed and the contemporary needs of Muslims today. With the hermeneutic interpretation model, he proposes four stages in his interpretation of the Qur’an, namely: meeting the world of the text, conducting critical analysis, finding the meaning of the text for its first recipient, and determining the meaning and application of the text for the present. Abdullah Saeed's idea is at least an alternative solution to address the contemporary challenges faced by Muslims today.